INTERNALISASI PENANAMAN ADAB DI MI MUHAMMADIYAH BALEHARJO PACITAN - Alwi, Itsnaini Muslimati; Khozin; Nurhakim, Moh. (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The problem of the younger generation that is often discussed is the decline in moral and ethical values. The phenomenon of the loss of adab, which is the loss of identity (the identity of Islamic sciences and the identity of Muslim scientists), is a common occurrence among the young Muslim generation. In response to this, education is needed to shape students' adab. The purpose of this paper is to discuss 1) Adab education that is internalized in MI Muhammadiyah Baleharjo, 2) Internalization of Adab in MI Muhammadiyah Baleharjo, 3) Challenges of Internalization of Adab in MI Muhammadiyah Baleharjo. The method used is a qualitative approach with a case study type of research. Data collection was done through observation and interviews. The results of this study include: 1) Adab internalized in MI Muhammadiyah Baleharjo includes adab in daily activities, 2) Internalization of adab is done through exemplary, habituation, storytelling, and reward and punishment by principals, teachers, and student guardians, 3) The challenge of internalizing rabbani character is the readiness of teachers to learn and patience in educating and providing good examples.